Endodontic retreatment of premolar with an impediment - Rosselle, Veronica Regina; Ongkowijoyo, Cendranata Wibawa; Setyabudi (Universitas Airlangga, 2023)
Background: Root canal treatment can fail due to several causes. One of them is root canal calcifications. Purpose: To explain root canal retreatment technique in premolar with calcification. Case(s): A 65 years old female patient came to universitas airlangga dental hospital with a chief complaint of pain on tooth number 34 and 35. Tooth number 34 and 35 had an old restoration with secondary caries. Both teeth did not respond to vitality test. Both teeth were tender on percussion and bite test. Surrounding soft tissue was normal. Radiograph image reveals inadequate root canal obturations on both teeth and a periapical lesion on tooth 35. Case Management: Old restoration and root canal filling material was removed, then root canal retreatment was performed. Subsequently the tooth was restored with fiber post and zirconia crown. Discussion: old restoration has to be removed gently in order to prevent further damage to tooth structure. Root canal filling material can be removed with heated instruments, solvent, and rotary instruments. After root canal filling material removal, the remaining root canals need to be thoroughly shaped, cleaned, and sealed. Conclusion: root canal retreatment on premolar with an impediment can be successfully performed with appropriate instruments, materials, and technique.